Reconciling Pro-Social vs. Selfish Behavior: Evidence for the Role of Self-Control - Peter Martinsson; Kristian Ove R. Myrseth; Conny Wollbrant (European School of Management and Technology (ESMT), 2010)
We test the proposition that individuals may experience a self-control conflict between short-term temptation to be selfish and better judgment to act pro-socially. Using a dictator game and a public goods game, we manipulated the likelihood that individuals identified self-control conflict, and we measured their trait ability to implement self-control strategies. Consistent with our hypothesis, we find that trait self-control exhibits a positive and significant correlation with pro-social behavior in the treatment that raises likelihood of conflict identification, but not in the treatment that reduces likelihood of conflict identification.
urn:nbn:de:101:1-2013071912604
Keywords: D01; D03; D64; D70; 650; self-control; pro-social behavior; altruism; experiment; Soziales Verhalten; Altruismus; Eigeninteresse; Spieltheorie; Test